2013
DOI: 10.1007/s11481-013-9518-9
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Depression Associated with HIV-1 Infection

Abstract: Antiretroviral therapy has greatly extended the lifespan of people living with human immunodeficiency virus (PLHIV). As a result, the long-term effects of HIV infection, in particular those originating in the central nervous system (CNS), such as HIV associated depression, have gained importance. Animal models for HIV infection have proved very useful for understanding the disease and developing treatment strategies. However, HIV associated depression remains poorly understood and so far there is neither a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 165 publications
0
3
0
6
Order By: Relevance
“…Little is known about the effects of HIV-related proteins including TAT on depression-like behaviour in animal models, which remains an unmet need in HIV-related basic science research (Barreto et al, 2014). In the present study, we demonstrated that TAT protein expression led to a significant elevation in reward thresholds reflecting anhedonia.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the effects of HIV-related proteins including TAT on depression-like behaviour in animal models, which remains an unmet need in HIV-related basic science research (Barreto et al, 2014). In the present study, we demonstrated that TAT protein expression led to a significant elevation in reward thresholds reflecting anhedonia.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia-induced neuroinflammation may be particularly responsible for this depression, given that the virus rapidly gains access to the brain where it infects mainly microglia (but not neurons) and induces their activation [26]. Studies in experimental animals show that the virus sheds two specific proteins, gp120 (glycoprotein 120 kDa) and Tat (transactivator of transcription), which induce marked microglial activation [27,28] together with a depressive-like neurobehavioral syndrome [25,[27][28][29][30] that can be attenuated by anti-inflammatory drugs [28,29].…”
Section: The Role Of Microglial Activation In Illness-associated Deprmentioning
confidence: 99%
“…El primero se asocia a la infección misma por VIH: los efectos neuro-tóxicos directos del virus, la respuesta inmunológica del hospedero, el tratamiento de la infección y las co-morbilidades del paciente; el segundo, a las consecuencias sociales de vivir con la infección; y el tercero a la aparición de infecciones oportunistas, las que eran prevalentes antes del advenimiento de la TARV [20][21][22][23][24][25] . En esta revisión nos centraremos fundamentalmente en los dos primeros mecanismos.…”
Section: Mecanismos De Daño Neuro-psiquiátrico En Personas Con Infeccunclassified
“…En relación al efecto directo del virus sobre el sistema nervioso central (SNC), se ha visto que el VIH atraviesa la barrera hemato-encefálica (BHE) desde los ocho días después de la primoinfección 26 , adaptándose para generar reservorios persistentes en microglias, macrófagos y astrocitos, especialmente en las regiones subcorticales del cerebro 23,27 . Una vez allí, ciertas proteínas del virus, entre las que destacan la gp120 y la Tat, interactúan con el tejido nervioso, produciendo pérdidas dendríticas y apoptosis neuronal mediante la hiperactivación de vías glutamatérgicas mediadas por NMDAR (receptor Nmetil-D-aspartato), la inducción de disfunción mitocondrial y el aumento de calcio intracelular, entre otros 21,22 . Este proceso puede mantenerse, incluso, existiendo una supresión viral periférica, ya que los antivirales utilizados en la TARV tienen distintas capacidades para cruzar la BHE.…”
Section: Mecanismos De Daño Neuro-psiquiátrico En Personas Con Infeccunclassified
See 1 more Smart Citation